Successful scientific writing a step-by-step guide for the biological and medical sciences - Matthews, Janice R. 1943- (Cambridge University Press, 2014)
Thoroughly revised and updated, the new edition of this acclaimed and best-selling guide offers a rich blend of practical advice and real-life examples. The authors draw on fifty years of experience, providing detailed step-by-step guidance designed to help students and researchers write and present scientific manuscripts more successfully through knowledge, practice, and an efficient approach. Retaining the user-friendly style of the previous editions, this fourth edition has been broadened to include detailed information relevant to today's digital world. It covers all aspects of the writing process, from first drafts, literature retrieval, and authorship to final drafts and electronic publication. A new section provides extensive coverage of ethical issues, from plagiarism and dual publication to honesty in reporting statistics. Both the text and 30 hands-on exercises include abundant examples applicable to a variety of writing contexts, making this a powerful tool for researchers and students across a range of disciplines.